Far beyond Phagocytosis: Phagocyte-Derived Extracellular Traps Act Efficiently against Protozoan Parasites In Vitro and In Vivo. (30th June 2016) - Silva, Liliana M. R.; Muñoz-Caro, Tamara; Burgos, Rafael A.; Hidalgo, Maria A.; Taubert, Anja; Hermosilla, Carlos
Abstract : Professional mononuclear phagocytes such as polymorphonuclear neutrophils (PMN), monocytes, and macrophages are considered as the first line of defence against invasive pathogens. The formation of extracellular traps (ETs) by activated mononuclear phagocytes is meanwhile well accepted as an effector mechanism of the early host innate immune response acting against microbial infections. Recent investigations showed evidence that ETosis is a widely spread effector mechanism in vertebrates and invertebrates being utilized to entrap and kill bacteria, fungi, viruses, and protozoan parasites. ETs are released in response to intact protozoan parasites or to parasite-specific antigens in a controlled cell death process. Released ETs consist of nuclear DNA as backbone adorned with histones, antimicrobial peptides, and phagocyte-specific granular enzymes thereby producing a sticky extracellular matrix capable of entrapping and killing pathogens. This review summarizes recent data on protozoa-induced ETosis. Special attention will be given to molecular mechanisms of protozoa-induced ETosis and on its consequences for the parasites successful reproduction and life cycle accomplishment.